Piezoactive dense diphenylalanine thin films via solid-phase crystallization; Applied Materials Today; Vol. 26 - Romanyuk K. N. Konstantin; Slabov V. Vladislav; Alikin D. Denis; Zelenovskiy P. S. Pavel; Correia M. R. P. Maria Rosario; Keller K. Kirill; Ferreira R. A. S. Rute; Vasilev S. Semen; Kopyl S. Svitlana; Kholkin A. L. Andrei Leonidovich (2022, 2022)
Title screen